2008
DOI: 10.1038/modpathol.2008.51
|View full text |Cite
|
Sign up to set email alerts
|

S100A4 expression is associated with lymph node metastasis in papillary microcarcinoma of the thyroid

Abstract: The detection of papillary microcarcinomas of the thyroid is increasing due to frequent use of ultrasound and fine-needle aspiration biopsy. Although most of the papillary microcarcinomas remain quiescent and follow an indolent clinical course, some behave aggressively and metastasize early, giving rise to clinically significant disease. There have been few studies concerning factors predictive of lymph node metastasis in papillary microcarcinomas. We analyzed the expression of S100A4, cyclin D1, p27 and MUC1,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
47
1

Year Published

2009
2009
2014
2014

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 62 publications
(53 citation statements)
references
References 37 publications
4
47
1
Order By: Relevance
“…Thus, its prognostic value has been suggested (14-16). There are several recent published studies on the correlation between the survival rate and the increased expression of S100A4 in other types of human malignancies (17)(18)(19)(20)(21)(22)(23). These reports suggest that S100A4 is associated with the aggressiveness of cancer and it may play a role in the pathogenesis of advanced-stage cancer.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, its prognostic value has been suggested (14-16). There are several recent published studies on the correlation between the survival rate and the increased expression of S100A4 in other types of human malignancies (17)(18)(19)(20)(21)(22)(23). These reports suggest that S100A4 is associated with the aggressiveness of cancer and it may play a role in the pathogenesis of advanced-stage cancer.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that the positive cytoplasmic expression of S100A irrespective of its nuclear expression has a prognostic value in many human malignancies (9,11,12,14,16,21,22). Kicuchi et al reported that S100A4 could translocate between the cytoplasm and nucleus in ovarian cancer cells (19).…”
Section: Overall Survival Progression-free Survival -----------------mentioning
confidence: 99%
See 1 more Smart Citation
“…S100A4 expression has also been described in primary and metastatic melanoma [3,32,39]. Elevated S100A4 levels are associated with a more aggressive phenotype and a poor prognosis [11,18,26,36]. Due to its involvement in disease development and progression and its broad expression in the tumor microenvironment, S100A appears as an attractive target for cancer therapy that should allow the destruction of the tumor directly by targeting the cancer cells themselves and indirectly by destroying the supporting tumor stroma cells.…”
Section: Introductionmentioning
confidence: 99%
“…S100A4 itself has been implicated in disease development and progression, as it promotes the oncogenic phenotype of tumor cells. Its expression has been described for a variety of cancer entities, e.g., carcinoma of the breast [12,22,30,37,46,54], ovary [25], thyroid [23,36,57], esophagus [38], bladder [1,11], gallbladder [9], colon [53], colorectum [10,19], pancreas [2,40,45] and prostate [17], gastric cancers [14,26,55], lung [27,34], and brain cancers [44,52]. S100A4 expression has also been described in primary and metastatic melanoma [3,32,39].…”
Section: Introductionmentioning
confidence: 99%